Speech Deficiency Testing And Correction Technologies - qizi, Shakirova Salima Yusipbay (Journal of Higher Education and Academic Advancement, 2024)
Speech deficiency, a pervasive communication disorder affecting millions of individuals worldwide, poses significant challenges to personal and professional development, social integration, and overall quality of life. The prevalence of speech deficiencies, including stuttering, apraxia, and dysarthria, underscores the necessity for innovative testing and correction technologies. This article provides an in-depth examination of the latest advancements in speech deficiency testing and correction technologies, highlighting their significance, applications, and potential benefits.